Does the Gospel of John Have a High Christology? - Gaston, Thomas E. (Horizons in biblical theology, 2014)
John’s gospel is often presented as having a “high” Christology but are alternative readings possible or even more credible? In this essay I re-evaluate the foundations of the purported high Christology of John’s gospel in light of recent Johannine scholarship. I will argue that some conventional readings of John are precarious and common proof texts, when read properly, are more indicative of a low Christology. I will also acknowledge that some passages might indicate a high Christology and warrant further study. If the Gospel of John has, in fact, a low Christology then this has implications for both the dating of the gospel and its relevance for the quest for the historical Jesus.